2014
DOI: 10.1063/1.4867234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical substitution, magnetic field, and hydrostatic pressure effect on martensitic and intermartensitic transition in bulk Ni49-xCuxMn38Sn13(0.5≤ x ≤ 2) Heusler alloys

Abstract: A considerable metamagnetic shape memory effect without any prestrain in Ni 46 Cu 4 Mn 38 Sn 12 Heusler alloy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…This phenomenon can understood by the fact that the application of magnetic field helps align the magnetic moments of the martensitic variants, which may produce internal stress in the martensitic phase and compensate the tension effect generated by Pd(Pt) doping. A similar field dependence of IMT was reported in Ni-Cu-Mn-Sn30 and Ni-Mn-In-Sb alloys31, where IMT vanished at a higher magnetic field.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This phenomenon can understood by the fact that the application of magnetic field helps align the magnetic moments of the martensitic variants, which may produce internal stress in the martensitic phase and compensate the tension effect generated by Pd(Pt) doping. A similar field dependence of IMT was reported in Ni-Cu-Mn-Sn30 and Ni-Mn-In-Sb alloys31, where IMT vanished at a higher magnetic field.…”
Section: Resultssupporting
confidence: 81%
“…Ma et al observed an IMT in high pressure annealed Ni-Co-Mn-Sn alloy, which was attributed to the enhanced magnetoelastic coupling by the application of pressure19. Recently, IMT was observed in Ni-Cu-Mn-Sn alloys, and it was proposed that replacing Ni for Cu generates the internal stress in the alloys, which is responsible for instability in the structure of the martensitic phase30. All these results indicate that the stability of martensitic phases with different structure is sensitive to the pressure (external or internal, positive or negative).…”
Section: Resultsmentioning
confidence: 99%
“…4b), indicating that an incomplete MT with residual austenite even at 173 K. This phenomenon is consistent with some other Ni-Mn-based alloys 52,53 , implying that the complete MT might be difficult to be achieved supposing that slightly inhomogeneous composition distribution exists in the bulk alloy. Furthermore, the two successive magnetostructural transition processes (A → 10 M and A → 10 M + 6 M) in the present alloy are essentially different from the two successive martensite (MT) and intermartensite transition (IMT) occur in some other types of FMSMAs such as Ni 55.8 Mn 18.1 Ga 26.1 40 , Ni 50 Mn 34 In 12 Sb 4 54 and Ni 49−x Cu x Mn 38 Sn 13 (0.5 < x < 2) 55 alloys.
Figure 4 In-situ X-ray diffraction (XRD) patterns for Co6 alloy in the range 35° < 2θ < 50° during cooling ( a ) from 343 K to 283 K and ( b ) from 273 K to 173 K, respectively. The diffraction peaks marked by five-pointed star corresponds to the sample stage.
…”
Section: Resultsmentioning
confidence: 66%
“…In comparison to MT, the IMT usually occurs at a much lower temperature, resulting in two entirely separated transformations. Currently, the IMT associated with the change of magnetization has been continuously reported in a new type of FSMAs, such as Ni-Mn-In-Sb15, Ni-Co-Mn-Sn1617 and Ni-Cu-Mn-Sn18. For these alloys, the IMT and MT were mostly found to be closing upon each other and hence form two successive magneto-structural transformations161718.…”
mentioning
confidence: 99%
“…Currently, the IMT associated with the change of magnetization has been continuously reported in a new type of FSMAs, such as Ni-Mn-In-Sb15, Ni-Co-Mn-Sn1617 and Ni-Cu-Mn-Sn18. For these alloys, the IMT and MT were mostly found to be closing upon each other and hence form two successive magneto-structural transformations161718. Owing to the sequent magneto-structural couplings, such a kind of the multiple MSTs, compared with the intermediate phase in Ni-Mn-Ga alloys, can show more abnormal physical properties1617.…”
mentioning
confidence: 99%